2021
DOI: 10.1111/jan.14807
|View full text |Cite
|
Sign up to set email alerts
|

Examining the links between regular leisure‐time physical activity, sitting time and prefrailty in community‐dwelling older adults

Abstract: Aims To examine the relationship between leisure‐time physical activity, sitting time and prefrailty in community‐dwelling older adults. Design Cross‐sectional study. Methods Between February and July 2019, 539 individuals over age 60 were recruited in northern Taiwan. Demographic, medical history, physical activity and frailty data were analysed using descriptive statistics, chi‐square tests and logistic regression. Results The prevalence of prefrailty was 24.4%; 33.2% had regular leisure‐time physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…With reference to previous studies [ 3 5 , 8 – 11 , 21 , 25 ], age, gender, socio-economic status (i.e., family number, education, and perceived economic situation), health status (i.e., body mass index and chronic medical conditions), health behaviors (i.e., alcohol consumption, smoking status, and regular dental visits), mental functioning (i.e., depression and cognitive functioning), and social participation (i.e., community activities, paid work, and informal social interactions) [ 11 ] were selected as covariates that may be confounding factors of the association between LA and incident disability. A representative survey of non-institutionalized individuals aged 60 and over in Spain reported that perceived economic situation was significantly associated with the prevalence of disability [ 26 ].…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…With reference to previous studies [ 3 5 , 8 – 11 , 21 , 25 ], age, gender, socio-economic status (i.e., family number, education, and perceived economic situation), health status (i.e., body mass index and chronic medical conditions), health behaviors (i.e., alcohol consumption, smoking status, and regular dental visits), mental functioning (i.e., depression and cognitive functioning), and social participation (i.e., community activities, paid work, and informal social interactions) [ 11 ] were selected as covariates that may be confounding factors of the association between LA and incident disability. A representative survey of non-institutionalized individuals aged 60 and over in Spain reported that perceived economic situation was significantly associated with the prevalence of disability [ 26 ].…”
Section: Methodsmentioning
confidence: 98%
“…Depression was assessed by the 5-item short form of the Geriatric Depression Scale [27], and categorized as present (scores of 2-5) or absent (scores of 0-1). Cognitive functioning was assessed by the MDS Cognitive Performance Scale [28], and categorized as poor (scores of [1][2][3][4][5][6] or intact (a score of 0). Community activities included volunteer activities and neighborhood association activities, and were classified with or without par-Environmental Health and Preventive Medicine (2022) 27:16 ticipation.…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leisure-time physical activity (LTPA) was assessed using two questions modified from Gionet and Godin 27 and Chang et al:. 6 (1) “Have you done any LTPA for 30 min or more a day, with a significant increase in breathing or sweating, in the past six months?”; and (2) “If you have, how often do you do it?” Some of the activities that qualified as LTPA were brisk walking, social or folk dancing, and traditional Chinese health-promoting exercises. Regular LTPA was defined as performing moderate–vigorous exercise during leisure time for at least 30 min a day, five days a week, over the previous six months.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that regular leisure-time PA (LTPA) can prolong life and reduce all-cause, cardiovascular, and cancer mortality, as well as prefrailty and frailty. 6 , 7 , 8 , 9 , 10 To improve or maintain adequate physical performance, exercise training needs to be challenging and have multiple components. The 2018 Physical Activity Guidelines for Americans Committee (PAGAC) Scientific Report provides strong evidence that PA reduces the risk of fall-related injuries in older people by 32–40%, and this includes severe falls requiring medical care or hospitalization.…”
Section: Introductionmentioning
confidence: 99%